Influence of Microbes on Neutrophil Life and Death - Kobayashi, Scott D.; Malachowa, Natalia; DeLeo, Frank R. (Frontiers in Cellular and Infection Microbiology, 2017)
Neutrophils are the most abundant leukocyte in humans and they are among the first white cells recruited to infected tissues. These leukocytes are essential for the innate immune response to bacteria and fungi. Inasmuch as neutrophils produce or contain potent microbicides that can be toxic to the host, neutrophil turnover and homeostasis is a highly regulated process that prevents unintended host tissue damage. Indeed, constitutive neutrophil apoptosis and subsequent removal of these cells by mononuclear phagocytes is a primary means by which neutrophil homeostasis is maintained in healthy individuals. Processes that alter normal neutrophil turnover and removal of effete cells can lead to host tissue damage and disease. The interaction of neutrophils with microbes and molecules produced by microbes often alters neutrophil turnover. The ability of microbes to alter the fate of neutrophils is highly varied, can be microbe-specific, and ranges from prolonging the neutrophil lifespan to causing rapid neutrophil lysis after phagocytosis. Here we provide a brief overview of these processes and their associated impact on innate host defense.